Who Outplays the Market in Russia? - ОзорнинаОльга Викторовна; ЧирковаЕлена Владимировна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Authors: Elena Vladimirovna Chirkova National Research University The Higher School of Economics evchirkova@gmail.com Olga V. Ozornina National Research University The Higher School of Economics The article deals with the investment skill of the Russian mutual funds’ managers. The authors find that most managers do not possess investment skill as 90% of the funds do not outperform the market steadily. Three of the four applied methodologies revealed that in 2004–2009 there existed more successful funds during the booming market, while during the downturn the number of successful funds diminished significantly. There are only 3–4 funds out of 74 in the sample whose managers are able to outplay the market in the long run.